Attractiveness of Foreign Direct Investment: Case of Digital Economy - KAMBOU, Porobayiré; KHARISS, Mohammed (Revue Internationale des Sciences de Gestion, 2020)
Foreign direct investment is now one of the determinants of economic growth. Nowadays, however, we are witnessing the development of a new form of economy: the digital economy, whose mode of production differs from traditional modes of production. We are in the digital age and we are witnessing the birth of digital MNE. These giants of the digital economy are sometimes barely 20 years old (Facebook was created in 2004 and Google in 1998) and yet the capitalization of each of them flirts with $1 trillion. It therefore seems necessary to question the investment potential of the digital economy and especially how a territory can attract FDI from companies in the digital economy. By highlighting the specific characteristics of companies in the digital economy in terms of FDI, on the one hand, and, on the other hand, by proposing actions to be taken to attract these companies to a given territory, this paper aims to contribute to the development of theoretical solutions and reflections.